PERAN SERTA INSTITUT AGAMA ISLAM NEGERI (IAIN) PALU DALAM MENDORONG PERKEMBANGAN LEMBAGA KEUANGAN SYARIAH DI KOTA PALU - Uswatun Hasanah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2014)
Educational institutions have a role and a great responsibility in the economic development of Shariah. Educational institutions are expected to be a source of development and socialization of Sharia banking. The presence of Islamic financial institutions in the city of Palu at this time has not yet achieved so much. The existence of the Islamic financial institutions would have to get support from various parties, including the one of which is derived from Islamic Institute of Palu. Although not yet done optimally, however Islamic Institute Palu have participated in developing the presence of Islamic financial institutions in the city of Palu. This form of participation is through: Participation in providing human resources, Socialization of Islamic financial institutions, Involvement of the Islamic Institute Palu against Movement of Islamic Economics, To cooperate with Islamic financial institutions